Probability Selection of Dormitory House For Students - Yunisvita, Yunisvita; Imelda, Imelda; Bachri, Fachrizal; Adnan, Nazeli; Yuliana, Saadah (International Journal of Economics and Financial Issues, 2018)
This research aims to analyze the factors that determine the student probability to choose their residence between private boarding houses and Unsri dormitories. Using the Binomial Logistic Regression models of the 275 samples of student respondents of Unsri in Indralaya Campus, the probabilities to choose where to live in private boarding houses is significantly affected by the rental price, but the changes of the rental rates do not alter in the student probability to live in private boarding houses. The most decisive variable is the perception of the location such as the distance to the campus location, public facilities, entertainment, dining, efficiency motive and transportation costs. The negative sign of the value of perception of the location means that the better the perception of respondents about the location of residence will increase the possibility of choosing to stay at private the boarding house. Similarly, the increase in income will increase the likelihood of respondents to choose boarding house, while on the contrary when it comes to the the number of facilities. Keywords: Logistic Binomial, Boarding/Dormitories House, Rent Price, Income, Location JEL Classifications: D31, R3